Estrutura da comunidade de insetos (Arthropoda: Insecta) associados à Aechmea distichantha Lem. (Bromeliaceae). - Amadeo, Felipe Emiliano (2012)
Bromeliaceae-insects associations are particularly common in the neotropics and these organisms use bromeliads and their tank as shelter against adverse climatic conditions, foraging and mating sites and nurseries. The aim of this study was to survey the richness and abundance of the enotmofauna associated with Aechmea distichantha (Bromeliaceae), as well as to evaluate the influence of the rainfall, the plant vertical distribution and morphometric parameters on those attributes. The study was conducted at the left border of the Paraná River, which is characterized by the presence of several rocky walls that allow the establishment of the bromeliads. The samplings were performed in the year of 2010, with three samplings in the dry season and three in the rainy season, in three layers of the rock walls (lower, middle, and upper). A total of 72 samples were taken (four individuals of A. distichantha in each layer) in both periods. 8468 insects belonging to 11 orders and 67 morphospecies were collected, with immature (56%) dominating over adults (44%). Hymenoptera had the greater number of morphospecies in total community and was the most abundant both in total community and in the adult group. Coleoptera was the most abundant order among immature forms with Scirtidae being the most representative. ANOVA results showed that only immature morphospecies richness was significantly different among the strata (F(2,66)=3,7065, p=0,02982), while abundance significant results were not observed for any groups. Multiple regression results showed that among morphometric parameters, the bromeliad reservoir perimeter explained the abundance and richness of adult insects only. These results suggest that the distribution of the plants along the rocky wall (spatial variation) and the variation of the bromeliad reservoir perimeter were responsible for the alterations in the insect morphospecies groups. Phenological changes caused by the differentiated development of the bromeliads, which grow under different conditions of luminosity along strata, besides the microclimate and organic matter amount differences due to this stratification would be the most influent factors for the variation of immature morphospecies richnesss. As for the adults, an increase in bromeliad reservoir perimeter positively influences the richness and abundance, since it leads to an increase in resource availability and microhabitat, which make possible the coexistence of species with different ecological necessities in this environment.